2017
DOI: 10.1213/ane.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Delivery Systems Versus Manually Controlled Administration of Total IV Anesthesia: A Meta-analysis of Randomized Clinical Trials

Abstract: Bispectral Index Scale (BIS)-guided closed-loop delivery of anesthetics has been extensively studied. We performed a meta-analysis of all the randomized clinical trials comparing efficacy and performance between BIS-guided closed-loop delivery and manually controlled administration of total IV anesthesia. Scopus, PubMed, EMBASE, and the Cochrane Central Register of clinical trials were searched for pertinent studies. Inclusion criteria were random allocation to treatment and closed-loop delivery systems versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 29 publications
0
58
0
Order By: Relevance
“…Regarding technical performance, the results show that the system is within the internationally accepted parameters for this type of devices. The publications that evaluate them consider a MDAPE between 20 and 50% as acceptable (Pasin et al, 2017); in this study, it was 21%. The MDPE, whose clinically accepted value is 10-20% (Gan et al, 2014), was 10.7% in our study, just like wobble; ideally, this value should be as close as possible to zero, which did not occur in any of the study groups, increasingly supporting the idea that a computer system cannot replace the analytical capacity of an anesthesiologist when it is necessary to make major decisions and avoid deviations in anesthetic maintenance of patients.…”
Section: Discussionmentioning
confidence: 70%
“…Regarding technical performance, the results show that the system is within the internationally accepted parameters for this type of devices. The publications that evaluate them consider a MDAPE between 20 and 50% as acceptable (Pasin et al, 2017); in this study, it was 21%. The MDPE, whose clinically accepted value is 10-20% (Gan et al, 2014), was 10.7% in our study, just like wobble; ideally, this value should be as close as possible to zero, which did not occur in any of the study groups, increasingly supporting the idea that a computer system cannot replace the analytical capacity of an anesthesiologist when it is necessary to make major decisions and avoid deviations in anesthetic maintenance of patients.…”
Section: Discussionmentioning
confidence: 70%
“…Bispectral index has also been used to guide TIVA techniques using closed‐loop delivery systems. A recent meta‐analysis demonstrated that BIS‐guided delivery of TIVA may reduce propofol dose during induction, maintain a better target depth of anaesthesia and reduce recovery time compared with manual targets . This is an evolving area, and although it is acknowledged that low recorded BIS values may reflect increased patient frailty or sensitivity to anaesthetic agents (rather than excessive anaesthetic administration), correctly monitored and tailored anaesthetic depth seems fundamental for our patients.…”
Section: Depth Of Anaesthesiamentioning
confidence: 99%
“…A recent meta-analysis by Pasin et al has evaluated closed-loop devices for intravenous anaesthesia [53], and concluded to the superiority of closed-loop delivery vs manual delivery (total intravenous anaesthesia: TIVA) but not vs target controlled infusion (TCI), with lower doses of propofol needed for induction and more precisely maintained BIS targets. The performance of various administration mode was assessed by the combination of the median absolute performance error and the wobble index, which were both lower in the case of closed-loop systems than with manually controlled administration of TIVA (p for effect < 0.00001 and = 0.003 resp.).…”
Section: Evaluation Of Closed-loopsmentioning
confidence: 99%
“…A recent metaanalysis by Pasin et al used MDAPE and wobble as comparison means of various closed-loop anesthetic delivery systems, to which they added propofol total administered dose, maintenance of heart rate between 25% of baseline, maintenance of mean arterial pressure (MAP) between 25% of baseline, fall in MAP from baseline and ephedrine boluses [53]. Similarly to these adjuncts, Soltesz et Dumont proposed to add several clinically based indicators in order to characterize the quality of induction, maintenance and emergence phases of anaesthesia [56].…”
Section: Evaluation Of Closed-loopsmentioning
confidence: 99%